Will the steps taken by South African expatriates to circumvent section 10(1)(o)(ii) trigger the South African GAAR?ar? - Coetzee, E.S.M. (Liza) (University of Pretoria, 2024)
Mini Dissertation (MCom (Taxation))--University of Pretoria, 2021.